OPTIMASI BIAYA PENGIRIMAN ALAT TANGKAP IKAN MENGGUNAKAN METODE NORTH WEST CORNER (NWC) DAN SOFTWARE LINGO - Nurmala Rosalinda; Trinopi Melani; Wahyu Wardian; Muchammad Fauzi (LPPM Universitas Bina Bangsa, 2021)
The problem of high transportation costs is usually closely related to the selling value of the product to be marketed because it concerns the HPP of the product, so the selection of methods to minimize transportation costs needs to be done. The data obtained is data from a PT. X which has several agents that will market its products to consumers. The data is then processed using the North West Corner (NWC) method and continued with Lingo Software to optimize the cost of translation. The results obtained from both methods are Rp 177,000,000 using the North West Corner (NWC) method and Rp 171,200,000 using lingo software.